A deletion in the wapB promoter in many serotypes of Pseudomonas aeruginosa accounts for the lack of a terminal glucose residue in the core oligosaccharide and resistance to killing by R3‐pyocin. Issue 3 (30th June 2013) - Kocíncová, Dana; Lam, Joseph S.
Summary: Pseudomonas aeruginosa is an opportunistic human pathogen producing a variety of virulence factors. One of them is lipopolysaccharide, consisting of endotoxic lipid A and long‐chain O‐antigen polysaccharide, which are connected together through a short linker region, called core oligosaccharide. Chemical structures of the core oligosaccharide are well conserved, with one exception, in that certain strains of P. aeruginosa add a terminal glucose residue (Glc IV ) to core by a transferase reaction, due to the activity of a glucosyltransferase, WapB. Here, we investigated the regulation of wapB expression. Our results showed that while the majority of analysed genomes of P. aeruginosa contain wapB, many of these have a conserved identical 5‐nucleotide deletion in the upstream region that inactivated the promoter. This deletion is within the −10 hexamer that is recognized by a principle sigma factor (RpoD, or σ70) as proven by data from an electromobility shift assay. These results provide the molecular basis of why LPS core of many P. aeruginosa strains is lacking Glc IV . In addition, we show that absence of Glc IV due to an inactive wapB promoter confers resistance to killing by R3‐pyocin, a phage tail‐like bacteriocin of P. aeruginosa .